Inferior Alveolar Nerve Lateralization and Transposition for Dental Implant Placement. Part II: a Systematic Review of Neurosensory Complications - Boris Abayev; Gintaras Juodzbalys (Stilus Optimus, 2015)
Objectives: This article, the second in a two-part series, continues the discussion of inferior alveolar nerve lateralization/transposition for dental implant placement. The aim of this article is to review the scientific literature and clinical reports in order to analyse the neurosensory complications, risks and disadvantages of lateralization/transposition of the inferior alveolar nerve followed by implant placement in an edentulous atrophic posterior mandible. Material and Methods: A comprehensive review of the current literature was conducted according to the PRISMA guidelines by accessing the NCBI PubMed and PMC databases, as well as academic sites and books. The articles were searched from January 1997 to July 2014. Articles in English language, which included adult patients between 18 - 80 years of age who had minimal residual bone above the mandibular canal and had undergone inferior alveolar nerve (IAN) repositioning, with minimum 6 months of follow-up, were included. Results: A total of 21 studies were included in this review. Ten were related to IAN transposition, 7 to IAN lateralization and 4 to both transposition and lateralization. The IAN neurosensory disturbance function was present in most patients (99.47% [376/378]) for 1 to 6 months. In total, 0.53% (2/378) of procedures the disturbances were permanent. Conclusions: Inferior alveolar nerve repositioning is related to initial transient change in sensation in the majority of cases. The most popular causes of nerve damage are spatula-caused traction in the mucoperiosteal flap, pressure due to severe inflammation or retention of fluid around the nerve and subsequent development of transient ischemia, and mandibular body fracture.